The style as a factor of office building concentration locations in European cities = Czynnik stylu jako determinanta lokalizacji koncentracji budynków biurowych w europejskich miastach - Bocian, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Where should office building concentrations be located in cities? What kind of factors has an influence on its locations? The aim of the research is to examine factors of office locations in cities. Selected office building concentrations in European cities were investigated as case studies.
Keywords: office building; business district; urban composition; budynek biurowy; dzielnica biznesowa; kompozycja przestrzenna